Global Solutions for the Kuramoto-Sivashinsky Equation Posed on Unbounded 3D Grooves (Contemporary Mathematics, 2021)
Initial boundary value problems for the three-dimensional Kuramoto-Sivashinsky equation posed on unbounded 3D grooves (that may serve as mathematical models for wildfires) were considered. The existence and uniqueness of global strong solutions as well as their exponential decay have been established.
Keywords: kuramoto-sivashinsky equation, global solutions, decay in unbounded domains